(3OGeZI GdeHJOYjfs - (3YHO Gddg Hf YHO GdQMef GdZfGbj GdMfajs
(3ChdgG (B:s
(3GdMeO ddg GdPi gOGfG dgPG heG cfG dfgJOi dhdG Cf gOGfG Gddg CeG GdbSe GdChd abO PcQ GdTjN GdEeGe Hf ghGRf GdbTjQi Cf WQjb GdUhajI Ydi GdMbjbI s
(3BNQgG (B:s
(3QLGA Cf dGjSJghi GdTjWGf Hef Hbi hjJLfH ddHGbi Yf EJHGY gPg GdWGFaI GdMeO ddg QH GdYGdejf s
(3GSJcJHg deWGdYJg YHO Gddg Hf YHO GdQMef GdTgjQ HCUjd GdehGYXs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdJUha hGdBOGH GdTQYjIs